Reformulasi Eksekusi Kebiri Kimia Guna Menjamin Kepastian Hukum Bagi Tenaga Medis/Dokter Dan Perlindungan Hukum Bagi Pelaku Pedophilia - Ari Purwita Kartika; Muhammad Lutfi Rizal Farid; Ihza Rashi Nandira Putri (Fakultas Hukum Universitas Islam Indonesia, 2020)
This research focuses on establishing chemical castration as additional criminal penalty. Chemical castration is intended to minimize sexual crimes against children. However, this additional punishment of chemical castration is conflicted with the ethics of the medical profession and the additional punishment of chemical castration is due to the lack of technical instructions for chemical castration. This is a type of normative legal research. This study concludes that: first, the regulation on the executor of the perpetrator of sexual crimes against children does not have legal certainty. A person who takes action on chemical castration is not only a person who does it, but a person who has knowledge in the field of chemical castration. This science is related to medical science which should be able to perform chemical castration. The act of chemical castration that should be done by a doctor conflicts with the professional code of ethics of a doctor. Second, the legislators must reconstruct the rules related to the implementation of chemical sanctions castration so that they are clearly regulated and do not conflict with other regulations.